Crawl positioning improves set-up precision and patient comfort in prone whole breast irradiation - Deseyne, Pieter (Sci Rep, 2020)
Prone positioning for whole-breast irradiation (WBI) reduces dose to organs at risk, but reduces set-up speed, precision, and comfort. We aimed to improve these problems by placing patients in prone crawl position on a newly developed crawl couch (CrC). A group of 10 right-sided breast cancer patients requiring WBI were randomized in this cross-over trial, comparing the CrC to a standard prone breastboard (BB). Laterolateral (LL), craniocaudal (CC) and anterioposterior (AP) set-up errors were evaluated with cone beam CT. Comfort, preference and set-up time (SUT) were assessed. Forty left and right-sided breast cancer patients served as a validation group. For BB versus CrC, AP, LL and CC mean patient shifts were − 0.8 ± 2.8, 0.2 ± 11.7 and − 0.6 ± 4.4 versus − 0.2 ± 3.3, − 0.8 ± 2.5 and − 1.9 ± 5.7 mm. LL shift spread was reduced significantly. Nine out of 10 patients preferred the CrC. SUT did not differ significantly. The validation group had mean patient shifts of 1.7 ± 2.9 (AP), 0.2 ± 3.6 (LL) and − 0.2 ± 3.3 (CC) mm. Mean SUT in the validation group was 1 min longer (P < 0.05) than the comparative group. Median SUT was 3 min in all groups. The CrC improved precision and comfort compared to BB. Set-up errors compare favourably to other prone-WBI trials and rival supine positioning.